Pengaruh Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Parlindungan, Parlindungan (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to examine the effect of tax planning on earnings management in pharmaceutical companies listed on the Indonesia Stock Exchange. This type of research is associated with quantitative data types, as well as secondary data sourced which is assessed from the financial side of pharmaceutical companies listed on the Indonesia Stock Exchange. This study used a sample of 10 pharmaceutical companies listed on the Indonesia Stock Exchange. This study uses descriptive statistics and simple linear regression for data analysis. The results of this study indicate that tax planning has no significant effect on earnings management in pharmaceutical companies listed on the Indonesia Stock Exchange